2010
DOI: 10.18806/tesl.v28i1.1062
|View full text |Cite
|
Sign up to set email alerts
|

On the Relationship of Multiple Intelligences With Listening Proficiency and Attitudes Among Iranian TEFL University Students

Abstract: Gardner’s (1983) Multiple Intelligences Theory (MIT) has been found to have profound implications in teaching English as a foreign language (TEFL) in that it provides a way for teachers to recognize learners’ individual cognitive and affective differences by providing favorable motivational conditions for learning. However, little investigation has focused on the domains of cognition and affect in a single study. Therefore, this study investigates two facets: the relationship of Multiple Intelligences (MIs) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…They learnt best through group work, team involvement and sharing their ideas. These results are consistent with Naeini & Pandian (2010) and Kok (2013) who clarified the relationship between listening comprehension and multiple intelligences. Listening is a complex and an active process of receiving and giving feedback to verbal and sometimes nonverbal messages.…”
Section: Discussion Of the Resultssupporting
confidence: 92%
“…They learnt best through group work, team involvement and sharing their ideas. These results are consistent with Naeini & Pandian (2010) and Kok (2013) who clarified the relationship between listening comprehension and multiple intelligences. Listening is a complex and an active process of receiving and giving feedback to verbal and sometimes nonverbal messages.…”
Section: Discussion Of the Resultssupporting
confidence: 92%
“…The findings indicate that there is a positive correlation between MI and listening achievements. The research conducted by Naeini and Pandian (2010), and Davoudi and Chavosh (2016) explores the way in which multiple intelligences and listening self-efficacy scores are linked. The findings from both studies indicate a positive correlation.…”
Section: The Influence Of MI In L2 Listening Acquisitionmentioning
confidence: 99%
“…There are some studies which were done in the area of intelligence and different components of language. For example in a study, Naeini and Pandian (2010) investigated the relationship between MI and listening proficiency. They found that there is no significant relationship between MI and listening.…”
Section: Reliabilitymentioning
confidence: 99%